(untitled) (Global Journal of Human-Social Science, 2023)
Japanese Zen Buddhism has led the way for Japanese aesthetics and has continued to bring this aesthetic to the public most notably in the form of ukiyo-e Zen Buddhism is a branch of Buddhism with the core principle of no thought no appearance no dwelling and Katsu as its practice from Linji School As Zen became integrated into Japanese life meditation was likewise manifested in social life most notably in the Edo period As a declining last feudal period in Japanese history the Edo Shogunate was flawed in terms of notification The samurai class which was attached to the Shogunate was fundamentally lacking in subject matter and the Tokugawa family gave them the idea of Bushido but not its inner pillar Japanese merchants who had no status spent their money recklessly but gained confusion and emptiness Bijinga-e who specializes in painting Japanese geisha in Ukiyo-e shows all the meanings of Kong through the composition white space and the form of people in the painting Most impressionists in the nineteenth century expressed their emotions and imitated East Asian style artworks and only had the form but not the spirit This paper thus concludes that the status of Kong in Japanese Zen aesthetics is like a butterfly in an invisible net out of control and out of sight Japanese Zen Buddhism has led the way for Japanese aesthetics and has continued to bring this aesthetic to the public most notably in the form of ukiyo-e Zen Buddhism is a branch of Buddhism with the core principle of no thought no appearance no dwelling and Katsu as its practice from Linji School As Zen became integrated into Japanese life meditation was likewise manifested in social life most notably in the Edo period As a declining last feudal period in Japanese history the Edo Shogunate was flawed in terms of notification The samurai class which was attached to the Shogunate was fundamentally lacking in subject matter and the Tokugawa family gave them the idea of Bushido but not its inner pillar Japanese merchants who had no status spent their money recklessly but gained confusion and emptiness Bijinga-e who specializes in painting Japanese geisha in Ukiyo-e shows all the meanings of Kong through the composition white space and the form of people in the painting Most impressionists in the nineteenth century expressed their emotions and imitated East Asian style artworks and only had the form but not the spirit This paper thus concludes that the status of Kong in Japanese Zen aesthetics is like a butterfly in an invisible net out of control and out of sight